Key CSR dimensions for the food chain - Forsman-Hugg, Sari; Katajajuuri, Juha-Matti; Riipi, Inkeri; Mäkelä, Johanna; Järvelä, Katja; Timonen, Päivi (Emerald, 2013)
Purpose - This paper aims to identify and define the content of corporate social responsibility (CSR) for the food chain. Design/methodology/approach - A qualitative research approach was applied in the study, based on participatory and case study research methodologies. The study drew on three different case food products and their supply chains: rye bread, broiler chicken products and margarine. The content of CSR was built through participatory workshops, the aim of which was to elicit the ideas of different stakeholder groups. Findings - The study identified seven key dimensions of food chain CSR: environment, product safety, corporate nutritional responsibility, occupational welfare, animal health and welfare, local market presence and economic responsibility. Originality/value - The results provide food and agribusiness companies with a better understanding of core CSR issues and their relevance in complex chains and networks. This may encourage the companies to promote their activities in a more responsible and sustainable direction and offer elements to build sustainable business cases. In addition, the results may indicate a change towards broader understanding of what is meant by corporate social responsibility.
Keywords: MA; ympäristövastuu; sosiaalinen vastuu; taloudellinen vastuu; sidosryhmädialogi; ruokaketjut; food chains; economic responsibility; environmental responsibility; social responsibility; stakeholder dialogue; stakeholders; corporate social responsibility; yhteiskuntavastuu; sidosryhmät; vastuullisuus